Megadome Evolution in The Ottoman’s Mosques; The Links - Idham, Noor Cholis; Numan, İbrahim (University of Malaya, 2020)
A long history of civilization through various cultural and technological influences, had shaped the Ottoman mosque architecture. Each of the objects has its unique characteristics yet connected each other. This paper examines how the classic Turkish mosque-dome architecture, have evolved by proposing examination on configuration similarities and its connection. The authors address 23 mosques in the high classical period of the Ottoman's era to reveal spatial and technical considerations of the main building. The dynasty's route in architecture from central Asia, Seljuk, Bursa, Edirne, and Istanbul is the context of the discussion. It is undeniable that the development of dome architecture in classical Turkey shows some clear linkages from the previous to the later age. Furthermore, some links connected pre and after Istanbul conquest, which contribute to clarify the dispute of the novelty of the architecture, were discovered.
Keywords: Ottoman Mosque; Dome Structure; Islamic Architecture; Architectural Evolution